Female Empowerment and Male Backlash: Experimental Evidence from India - Claire Cullen; Sarthak Joshi; Joseph Vecci; Julia Talbot-Jones (Institute of Labor Economics (IZA), 2024)
Public spending on gender equality and women's empowerment is rising rapidly in many countries. However, the unintended consequences of women's empowerment is rarely measured and remains poorly understood. We study the impact of female empowerment programs on male backlash through a series of experiments involving 1,007 households in rural India. The paper has four key parts. First, we use an experiment to measure backlash, observing men's decisions to financially penalize women who participated in empowerment programs. We find that men pay to punish empowered women at double the rate of women in an otherwise identical control group (17 percent versus 8 percent). We also show that men engaging in backlash tend to hold more conservative gender attitudes and are more likely to accept or commit intimate partner violence. Second, we test multiple theories on the conditions that trigger backlash and find that backlash occurs regardless of how women become empowered. Third, we examine social image concerns as a potential behavioral mechanism and find that 18 percent of men are willing to pay to conceal their household's involvement in empowerment programs. Those who choose to conceal are more likely to engage in backlash, suggesting that reputational concerns play a key role in driving this behavior. Finally, we test several policies to reduce backlash and find that reframing empowerment programs to emphasize broader community benefits can help mitigate backlash.
Keywords: C93; J12; J16; O12; 330; male backlash; female empowerment; social image; norms; experiments